CONFLICT, COMMUNITY AND THE 'NATIONAL' AUDIENCE: REMEMBERING TURKISH CYPRIOT CINEMAGOING IN 1950s NICOSIA. Issue 4 (1st October 2020) - Stubbs, Jonathan; Boğaç, Barçın
Abstract : Drawing on oral history interviews, contemporary newspaper sources and the archives of the British colonial administration, this article examines the experiences of the Turkish Cypriot cinema audience in Nicosia, the capital city of Cyprus, during the 1950s. This period was marked by rising anti-colonial and intercommunal conflict, but film exhibition nevertheless flourished and the cinema played a substantial role in the social, economic and political lives of many Turkish Cypriots. Memories of cinemagoing in Nicosia are marked by the experience of British colonial power, but they also reflect commercial interactions with the city's more dominant Greek Cypriot community. The encounter with Turkish culture through the viewing of films imported from Turkey also contributed to the development of nationalist political aspirations. As Nicosia's Turkish and Greek communities became increasingly polarised, cinemagoing experiences were influenced more and more by external political events. Nevertheless, the cinema of the 1950s is remembered as a communal, egalitarian and romantic space which provided the means to escape from everyday tensions.